2011
DOI: 10.1088/0953-8984/23/24/246001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order in orbital models of the iron pnictides

Abstract: We examine the appearance of the experimentally-observed stripe spin-density-wave magnetic order in five different orbital models of the iron pnictide parent compounds. A restricted meanfield ansatz is used to determine the magnetic phase diagram of each model. Using the random phase approximation, we then check this phase diagram by evaluating the static spin susceptibility in the paramagnetic state close to the mean-field phase boundaries. The momenta for which the susceptibility is peaked indicate in an unb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 107 publications
(371 reference statements)
2
40
0
Order By: Relevance
“…The leading instability of the system upon decreasing T is into a state with φ * corresponding to the maximum of the left-hand side of Eq. (23). A simple analysis shows that the maximum is at φ * = 0 for α ≥ 2 and at a finite φ * for 1 < α < 2 (see Fig.…”
Section: The Case D =mentioning
confidence: 91%
See 1 more Smart Citation
“…The leading instability of the system upon decreasing T is into a state with φ * corresponding to the maximum of the left-hand side of Eq. (23). A simple analysis shows that the maximum is at φ * = 0 for α ≥ 2 and at a finite φ * for 1 < α < 2 (see Fig.…”
Section: The Case D =mentioning
confidence: 91%
“…Orbital Order ARPES measurements on detwinned samples have found that the onset of resistivity anisotropy is accompanied by the onset of orbital order in the paramagnetic phase, with different occupations for the d xz and d yz orbitals 10 . One possibility, explored by several authors in different contexts, is that this orbital ordering is an intrinsic instability of the system [18][19][20][21][22][23][24]26,27 . In line with the theme of this work, we explore another possibility, namely that the orbital order is induced by the Ising-nematic order.…”
Section: Consequences Of the Ising-nematic Ordermentioning
confidence: 99%
“…23 The FSs of the two-and three-orbital models in the AFM state at half filling are shown in Fig. 1.…”
Section: Modelmentioning
confidence: 99%
“…Another alternative explanation was given by or-bital ordering. [32][33][34][35][36][37][38][39][40][41][42][43][44] In this scenario, the interactions between orbitals drive local ordering in orbital occupancy, and resulting in rotational symmetry breaking. However, all of these consequences are similar to our approach.…”
Section: 1229mentioning
confidence: 99%